Adaptive English Learning Materials during Covid 19 in Indonesian School - Theresia Nera Sunny; Sri Sumarni; Darmahusni Darmahusni (Universitas Muhammadiyah Semarang, 2023)
As a result of Covid-19, changes have been made across all sectors ofsociety, including higher education. Thus, educators should have the abilityand the resources necessary during the pandemic to provide effectivelearning materials and methods to students. Learners are able to recognizethe characteristics of English materials, which facilitates and accelerates theacquisition of the language. As a result, learning materials play an importantrole in defining educational goals, and quality education cannot beseparated from the curriculum. While educational materials play a rolewithin and outside of the classroom, they also play a role in influencingstudents. Therefore, changes to educational materials should continue to bemade in order to improve education quality, while ensuring that thesechanges do not interfere with learning. This study examines the adaptiveEnglish-learning materials that Indonesian schools have used duringCOVID-19. Based on the results of 10 journals that have applied adaptiveEnglish learning materials in Indonesian schools, the materials have beendeveloped. This research was conducted using instruments published inscientific journals. Students from Indonesian schools were the subjects ofthe study. During this research, the following steps were taken: a collectionof published journals, Surveying and analyzing the needs of the students,planning, writing the course grid, and evaluating the course materials areall necessary. This study used a qualitative methodology to identify theavailability of adaptive English learning materials in Indonesian schoolsfrom 2019 to 2022. This journal reported that many educators and studentswere satisfied with the adaptive English learning materials developed byeducators. Therefore, educators must be creative in order to achievestudents' success, especially in terms of their ability to learn languages in anew curriculum called Kurikulum Merdeka. It is possible for educators touse adaptive learning in the Kurikulum Merdeka in order to maximize theeffectiveness of teaching and learning activities